Study of Expression of COX-2 and HER2/neu in Colorectal Cancer and Their Correlation with Histological Grades - Vandana Yadav (Annals of Pathology and Laboratory Medicine, 2025)
Background: Colorectal cancer (CRC) is a significant global health concern with increasing incidence and poor prognosis in advanced stages. This study evaluates HER2/neu and COX2 expression, key biomarkers in CRC, using immunohistochemistry. Their correlation with age, sex, tumor location, and histological grade is analyzed to refine diagnosis and guide personalized treatment. Materials and Methods: Fifty resected colorectal carcinoma specimens diagnosed between January 2019 and December 2023 at J.L.N. Medical College, Ajmer, were analyzed. Immunohistochemical staining was performed using a rabbit monoclonal antibody for HER2/neu and a rabbit polyclonal antibody for COX2. Expression levels were correlated with clinicopathological parameters. Results: Patients ranged from 20 to 82 years (mean: 55.6), with a male predominance. The rectum and caecum were the most common tumor sites. Adenocarcinoma accounted for 76% of cases, with grade II being most frequent (63.16%). HER2/neu overexpression was observed in 26% of cases, significantly correlating with serosal invasion, lymph node involvement, histological grade, and stage. COX2 overexpression occurred in 70% of cases, also showing significant associations with these factors. A strong positive correlation was noted between HER2/neu and COX2 expression. Conclusion: HER2/neu and COX2 overexpression contribute to CRC progression, aiding in tumor invasion and metastasis. Targeting these markers, alone or with standard therapies, offers a promising strategy for personalized CRC treatment. COX2 inhibition may also play a role in prevention and therapy.